The incidence of malocclusions in children at the “ugly duckling” stage - Masłowska-Kasowicz, Anna; Nowicka-Dudek, Katarzyna; Zadurska, Małgorzata; Shybinsky, Volodymir; Lesitskiy, Markiyan; Chukhray, Natalya (Forum Ortodontyczne / Orthodontic Forum, 2019)
Late childhood is one of stages of masticatory organ development and it is the period when deciduous teeth are replaced with permanent teeth. Physiological diastema, namely a gap between upper medial incisors, and the position of these teeth in protrusion and distoinclination, is a normal phenomenon and it is commonly referred to as the “ugly duckling” stage. Aim. The main aim of the study was to assess occlusal conditions in school children aged 8 years. An additional aim – to determine the incidence of premature loss of deciduous molars and canines. Material and methods. 305 school children aged 8 years were subject to screening tests. The clinical examination included extraoral evaluation of the face and intraoral evaluation of occlusion. Results. Normal occlusion was observed in 17.4% of subjects. In most cases normal extraoral features were also observed. Malocclusions of various intensity affected 82.6% of children. Teeth crowding and class II malocclusions were the most common malocclusions – 61.6% and 11.8% of subjects, respectively. Divergent diastema was the most common diastema, and it is a characteristic feature in children in this developmental period. The premature loss of deciduous canines and molars is significant. Absence of deciduous teeth was found in every third child, while absence of deciduous molars was found in every second child. Conclusions. The analysis of occlusal conditions in children aged 8 years indicates a high incidence of malocclusions and reveals the need for a wider access to orthodontic services for patients in the “ugly duckling” stage. It also indicates the need to introduce activities to prevent or interrupt the development of malocclusions in the early period of replacement of deciduous dentition with permanent teeth. (Masłowska- Kasowicz A, Nowicka-Dudek K, Zadurska M, Shybinskyy V, Chukhray N, Lesitskiy M. The incidence of malocclusions in children at the “ugly duckling” stage. Orthod Forum 2019; 15: 14-26).